Citrus Pest Quick Guide: Brown Soft Scale - Lauren Diepenbrock; Jamie D Burrow (EDIS)
A one-page quick guide written by Lauren M. Diepenbrock and Jamie D. Burrow and published by the Entomology and Nematology Department presents the life cycle of brown soft scale and provides several photos of the pest and the damage it causes to assist in identification. https://edis.ifas.ufl.edu/in1252